Analisa Moda Entri (Entry Mode) Untuk Pemasaran Produk Tekstil - Aisyah Pia Asrunputri; Arif Widodo Nugroho (POLITEKNIK LP3I JAKARTA, 2023)
With trade that does not know cross borders, many companies sell their products or services abroad. Cambric Textiles is one of the companies from Indonesia that chooses export as an entry mode to expand its market share expansion globally. Strengthened by capabilities, achievements and experience in doing business, Cambric has a strategy of staying in the global market. The creation of competitiveness as well as a sustainable business is one of the biggest objectives for the company. Of course, with approaches and methods that can support the achievement of these objectives.Keywords: Cambric Textiles, Global Market, Sustainable Business, Competitiveness, Export